The Analysis of the Impact of AI Utilization in Creating Ghibli-Style Visual Effects on the Creative Industry: Analisis Dampak Penggunaan Kecerdasan Buatan (AI) dalam Pembuatan Efek Visual Gaya Ghibli terhadap Industri Kreatif - M. Nazir Arifin; Moch. Amir Mahmud; Farras Maulana Haris; Moh. Hairul Ramadhan (Brilliance: Research of Artificial Intelligence, 2025)
The emergence of artificial intelligence (AI) has opened new creative possibilities, particularly in the visual arts. This study investigates the impact of utilizing AI-generated illustrations in the style of Studio Ghibli on the creative industry. The research aims to explore how such technology influences creative workflows, aesthetic values, and public reception. A qualitative approach was employed through interviews with illustrators, animation professionals, and digital content creators, combined with a case study analysis of AI-generated Ghibli-style artworks. The findings indicate that AI tools not only accelerate the production process but also inspire new forms of artistic expression. However, concerns were raised regarding originality, intellectual property rights, and the potential displacement of human artists. Despite these challenges, most respondents acknowledged the potential of AI as a collaborative tool rather than a replacement. This study concludes that the integration of Ghibli-style AI art into the creative industry can be a catalyst for innovation while also demanding adaptive strategies from practitioners and policy makers alike.